Gender Power Dynamics within Bureaucratic Structures: An Analysis of Institutional Patriarchy and Hegemonic Masculinity at the DP3AKKB of Banten Province - Aisyah Machiqa Ilmi; Brigita Putri Marito; Ika Arinia Indriyany (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the dynamics of gender power relations within bureaucratic structures through the perspectives of institutional patriarchy and hegemonic masculinity in the Department of Women’s Empowerment, Child Protection, Population and Family Planning (DP3AKKB) of Banten Province. The research employs a qualitative method with a case study approach. Data were collected through literature review and document analysis of official institutional documents, including strategic plans, performance reports, and organizational staffing data. Data were analyzed qualitatively using thematic reading and critical interpretation to identify patterns of position distribution, leadership practices, and organizational culture shaping gender relations in the bureaucracy. The findings indicate that women hold a strong numerical representation in the leadership structure of DP3AKKB, with the majority of strategic positions occupied by female officials. However, the hierarchical organizational structure and bureaucratic leadership norms emphasizing authority, seniority, and administrative rationality still reflect the influence of masculine values in leadership legitimacy. This condition creates an institutional paradox in which an institution mandated to promote gender equality continues to operate within a bureaucratic framework that potentially reproduces gendered power relations. The study suggests that gender equality in bureaucracy cannot be measured solely by women’s numerical representation but also requires transformation in organizational culture and substantive power distribution in decision-making processes.